‘Usul mikul’, ‘Ketiban sampur’, and the atrophy of innovation process - Rocky Adiguna; Nofie Iman; Rokhima Rostiani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
Idea sharing is one of the most common ways of developing innovation in organizations. Aspirations and suggestions for improvements are recognized, discussed, and executed through idea sharing. This study adopts an ethnographic approach and critically analyzes how idea sharing goes against the grain of organizational culture. Based on a study of a higher education institution in Java, Indonesia, the paper highlights usul mikul and ketiban sampur as two modes of cultural practice which, over time, penalize innovators in their efforts to initiate change and renewal. The results show that these practices are formative to organizational atrophy. They weaken organizational capability to innovate due to the disuse of members’ capabilities. Importantly, the study contributes to the growing literature on innovation management, organizational culture, and higher education management.